(untitled) (Research, Society and Development, 2022)
Family businesses have a high importance in the development of the economy, since they represent a significant part of the GDP (gross domestic product) and are responsible for generating millions of jobs worldwide. The management of all companies has some common purposes, but family-owned companies have certain peculiarities due to their close ties. The objective was to present important aspects in the management of family businesses, approaching subjects that could represent challenges in their management and proposing methods for their resolution. The methodological processes used were qualitative, exploratory, descriptive, and bibliographic. The succession process, the importance of tradition and family’s values, and decision making were evaluated in the literature. The results indicate that an efficient succession process depends on the successor’s planning and professionalization. It was concluded that there are effective methods established to support the decision making of family businesses in order to minimize the influence of conflicts of interest of the family. And the present work also highlights the importance of preserving the values of the family organization.